Pain and Neuropathic Pain in Rheumatic Diseases - Seifert, Olga; Baerwald, Christoph (Aktuelle Rheumatologie, 2020)
Pain is a challenge to rheumatologists. Not only patients with active arthritis but also patients with a good therapeutic response and even in remission complain of persistent joint pain. It has been proposed that a chronic pain stimulus may have a greater impact in a chronic inflammatory state, and the process towards a pain condition may be influenced by individual predisposition for development of chronic pain. In addition, features of peripheral pain processing may be exacerbated by inflammation, and disturbed pain processing may be a feature contributing to widespread pain. Furthermore, a neuropathic component may be part of the total pain experience of our patients. There are many different strategies of pain therapy in patients with rheumatic diseases, such as pharmacological and non- pharmacological modalities.
Keywords: pain; rheumatic disease; neuropathic pain